Full-Duplex mmWave Communication with Hybrid Precoding and Combining - R. López-Valcarce; M. Martínez-Cotelo (European Signal Processing Conference (EUSIPCO), 2020)
We investigate the design of hybrid precoders and combiners for a millimeter wave (mmWave) point-to-point bidirectional link in which both nodes transmit and receive simultaneously and on the same carrier frequency. In such full-duplex configuration, mitigation of self-interference (SI) becomes critical. Large antenna arrays provide an opportunity for spatial SI suppression in mmWave. We assume a phase-shifter based, fully connected architecture for the analog part of the precoder and combiner. The proposed design, which aims at cancelling SI in the analog domain to avoid frontend saturation, significantly improves on the performance of previous approaches.
Keywords: full-duplex; mmWave; rodin; winter